Exercise and Adipose Tissue Immunity: Outrunning Inflammation. Issue 5 (26th April 2021) - Winn, Nathan C.; Cottam, Matthew A.; Wasserman, David H.; Hasty, Alyssa H.
Abstract : Chronic inflammation is considered a precipitating factor and possibly an underlying cause of many noncommunicable diseases, including cardiovascular disease, metabolic diseases, and some cancers. Obesity, which manifests in more than 650 million people worldwide, is the most common chronic inflammatory condition, with visceral adiposity thought to be the major inflammatory hub that links obesity and chronic disease. Adipose tissue (AT) inflammation is triggered or heightened in large part by (1) accelerated immune cell recruitment, (2) reshaping of the AT stromal‐immuno landscape (e.g., immune cells, endothelial cells, fibroblasts, adipocyte progenitors), and (3) perturbed AT immune cell function. Exercise, along with diet management, is a cornerstone in promoting weight loss and preventing weight regain. This review focuses on evidence that increased physical activity reduces AT inflammation caused by hypercaloric diets or genetic obesity. The precise cell types and mechanisms responsible for the therapeutic effects of exercise on AT inflammation remain poorly understood. This review summarizes what is known about obesity‐induced AT inflammation and immunomodulation and highlights mechanisms by which aerobic exercise combats inflammation by remodeling the AT immune landscape. Furthermore, key areas are highlighted that require future exploration and novel discoveries into the burgeoning field of how the biology of exercise affects AT immunity.